Um modelo de negociação para aquisição de habilidades cognitivas no contexto da educação matemática - Santos, Allan Gomes dos (2008)
This work of research has as presupposition the constructivism piagetiano, according to which, the construction of the knowledge constitutes in understanding the intellectual development of a person (PIAGET, 1973). It is about a study concerning one of the great challenges for Mathematical Education that is in using the subject it a way to reach the biggest point of the Education (D'AMBROSIO, 2004). In the relations of hypotheses we assume that, the negotiation in the learning search that all relation human being is, in certain way, a negotiation, therefore it involves commitments and they established conditions (MATOS, 1983). E, corroborating with this idea (FRANT & CASTRO, 2002), they defend that the learning is in the relation between the citizens for negotiation. Moreover, the persuasion in the learning is also focused, that deals with the envolvement to the speaker and the audience during the interlocution, envolvement in which the objective from the speaker is to obtain from the audience the adhesion to his thesis (PERELMAN & OLBRECHTS, 2002). Since then, there are so-called mental models, that are as cognitive blocks of construction that they can be combined and be recombined as necessary (JOHNSON, 1983). This research is based on theoretical principles. The theoretical implications search to present a proposal of change in learning process of Mathematical Education, through the modeling of an Environment of Systematic Learning (Paragua Project). Thus, in the search to improve the quality of education, this environment considers, the light of the theory of the constructivism, to favor the construction of the knowledge and to construct new cognitive abilities. On learning of mathematics this environment is the possibility "to consolidate the teachlearning", getting an education more playful and attractive based on mechanisms as the negotiation and persuasion in the learning and mental models, inside of a trustworthiness factor that envolves the main agents of the educational context, the professor and the student.